Data Mining Inspired Localized Resistivity in Global MHD Simulations of the Magnetosphere. Issue 2 (13th February 2023) - Arnold, H.; Sorathia, K.; Stephens, G.; Sitnov, M.; Merkin, V. G.; Birn, J.
Abstract: Recent advances in reconstructing Earth's magnetic field and associated currents by utilizing data mining of in situ magnetometer observations in the magnetosphere based on geomagnetic indices and solar wind parameters have proven remarkably accurate at reproducing observed ion diffusion regions. We investigate the effect of placing regions of localized resistivity in global simulations of the magnetosphere at specific locations inspired by the data mining results for the substorm occurring on 6 July 2017. When explicit resistivity is included, the simulation forms an x‐line at the same time and location as the Magnetospheric Multiscale Mission observation of an ion diffusion region at 15:35 UT on that day. Without this explicit resistivity, reconnection forms later in the substorm and far too close to Earth (≳−15 R E ), a common problem with global simulations of Earth's magnetosphere. A consequence of reconnection taking place farther down the tail due to localized resistivity is that the reconnection outflows transport magnetic flux Earthward and thus prevent the current sheet from thinning enough for reconnection to take place nearer Earth. As these flows rebound tailward from the inner magnetosphere, they can temporarily and locally (in the dawn‐dusk direction) stretch the magnetic field allowing for small scale x‐lines to form in the near Earth region. Due to the narrow cross‐tail extent of these x‐lines (≲5 R E ) and their short lifespan (≲5 min), they would be difficult to observe with in situ measurements. Future work will explore time‐dependent resistivity using 5 min cadence data mining reconstructions. Plain Language Summary: Recently, data mining of spacecraft magnetometers have created highly accurate reconstructions of Earth's magnetic field. These reconstructions capture the location and timing of so‐called x‐lines on the night side of Earth. Magnetic field lines reconnect at x‐lines and convert magnetic energy to plasma energy via heating and acceleration of flows. Nightside reconnection is a crucial part of geomagnetic storms and substorms that pose a danger to spacecraft, astronauts, and the power grid on Earth. By identifying x‐lines in reconstructions we can influence simulations of specific substorms to increase their accuracy and make them more physically realistic. We demonstrate this ability by matching simulation results with observations and find that reconnection further from Earth suppresses extended x‐line formation near Earth. Additionally, the flows from reconnection can bounce off the strong magnetic field close to Earth (a well‐known effect) and locally stretch the magnetic field creating small scale x‐lines near Earth. Key Points: Localized Resistivity in global magnetohydrodynamic simulations can "encourage" magnetic reconnection in specific locations to match data mining results Active x‐lines at X GSM ≲ −20 R E can suppress the formation of extended x‐lines at X GSM ≳ −15 R E Reconnection outflows rebound from the near‐Earth region causing transient and narrow (in Y GSM ) secondary reconnection